Penerapan Model Contextual Teaching and Learning untuk Meningkatkan Pemahaman dan Retensi Nilai Pancasila Kelas III - Latifah, Latifa; Sabrina, Nazwa; Widodo, Susilo Tri; Toba, Firdaus (YASIN, 2025)
Although context-based learning has been widely discussed in previous studies, research that specifically examines the simultaneous improvement of understanding and retention of Pancasila values through the application of the Contextual Teaching and Learning (CTL) model remains limited. This study aimed to analyze the effectiveness of CTL in enhancing the understanding and retention of Pancasila values among elementary school students. A quantitative approach with a one-group pretest–posttest design was employed, involving 16 third-grade students selected using a total sampling technique. Data were collected through a pretest, posttest, a retention test administered one week after instruction, and observations of the CTL implementation process, then analyzed using descriptive statistics and N-Gain calculations to measure the level of improvement in students’ understanding and retention. The findings indicated a significant increase in the understanding of Pancasila values, as reflected in higher scores from pretest to posttest and improved learning mastery. The retention test results showed that most students were able to maintain their understanding after a time delay, indicating that CTL is effective in strengthening long-term retention. These findings contribute to the development of contextual learning theory and broaden the understanding of value internalization processes at the elementary education level. The study underscores the importance of implementing CTL in Pendidikan Pancasila instruction and recommends that teachers employ contextual strategies to foster meaningful student understanding, while also opening opportunities for further research on the development of conceptual CTL models across broader educational contexts and levels.